Pengaruh E-Government dan Transparansi terhadap Kualitas Laporan Keuangan Pemerintah Daerah - As’syifa Qolbi Maharani; Rindu Rika Gamayuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to determine the influence of e-government and transparency on the quality of local government financial reports. The research method used is quantitative. The partial test results of this study show that e-government has a significant effect on the quality of local government financial reports, while transparency does not have a significant effect on the quality of local government financial reports. The simultaneous test results of this study indicate that e-government and transparency have a significant influence on the quality of local government financial reports.